Spatial and Temporal Patterns of Symbiont Colonization and Loss During Bleaching in the Model Sea Anemone Aiptasia - Tivey, Trevor R.; Coleman, Tyler J.; Weis, Virginia M. (Frontiers in Marine Science, 2022)
The ability of symbionts to recolonize their hosts after a period of dysbiosis is essential to maintain a resilient partnership. Many cnidarians rely on photosynthate provided from a large algal symbiont population. Under periods of thermal stress, symbiont densities in host cnidarians decline, and the recovery of hosts is dependent on the re-establishment of symbiosis. The cellular mechanisms that govern this process of colonization are not well-defined and require further exploration. To study this process in the symbiotic sea anemone model Exaiptasia diaphana, commonly called Aiptasia, we developed a non-invasive, efficient method of imaging that uses autofluorescence to measure the abundance of symbiont cells, which were spatially distributed into distinct cell clusters within the gastrodermis of host tentacles. We estimated cell cluster sizes to measure the occurrence of singlets, doublets, and so on up to much larger cell clusters, and characterized colonization patterns by native and non-native symbionts. Native symbiont Breviolum minutum rapidly recolonized hosts and rapidly exited under elevated temperature, with increased bleaching susceptibility for larger symbiont clusters. In contrast, populations of non-native symbionts Symbiodinium microadriaticum and Durusdinium trenchii persisted at low levels under elevated temperature. To identify mechanisms driving colonization patterns, we simulated symbiont population changes through time and determined that migration was necessary to create observed patterns (i.e., egression of symbionts from larger clusters to establish new clusters). Our results support a mechanism where symbionts repopulate hosts in a predictable cluster pattern, and provide novel evidence that colonization requires both localized proliferation and continuous migration.